Simulation and Economic Analysis of Biodiesel Production using Supercritical Methanol - Patle, Dipesh Shikchand; Phung , Eng Wei; Ahmad, Zainal (Taylor's University, 2015)
There is an increasing interest towards the use of vegetable oils (palm oil in Malaysia) in the much sought eco-friendly biodiesel production. This study focuses on the biodiesel production using supercritical methanol. The main highlights of this process include the un-necessity of catalyst and the insensitivity to the presence of free fatty acids and water in the feedstock. In this study, steady state simulation and sensitivity analysis of biodiesel production using supercritical methanol are performed. In the subsequent part, cost analysis is done using the Aspen Process Economic Analyzer. The feed oil is found to be the main contributor to the total manufacturing cost.